Analisis Kebutuhan Media Film Animasi sebagai Upaya Peningkatan Keterampilan Berpikir Historis Peserta Didik - Agry Pradiyas Sukma; Elfa Michellia Karima (Jurusan Sejarah FIS UNP, 2026)
This study aims to conduct a needs analysis on the use of innovative learning media in history subjects at SMAN 14 Padang. Students. Based on the results of classroom observations and interviews with teachers and students, information was obtained that the history learning process is still dominated by lecture methods and the use of textbooks. This condition causes students to be less active, have difficulty understanding the chronology of events, and have difficulty developing historical thinking skills. The needs analysis was conducted on four aspects, namely teacher conditions, student characteristics, availability of resources, and school facilities and infrastructure. The findings show that teachers have not utilized varied learning media, while students consider learning less interesting because it is limited to verbal explanations. Students need media that is contextual, interactive, and able to visualize historical events. Therefore, animated films are seen as relevant as an alternative learning media because they can increase motivation, clarify concepts, and support the development of students' historical thinking skills. This needs analysis becomes the initial basis for the development of animated film media based on the Independent Curriculum that is appropriate to the characteristics of 21st-century students.